Written word, public space and politics in Clorinda Matto de Turner - Mannarelli, María Emma (2020)
This article addresses the public and political participation of Clorinda Matto de Turner, from the written word, in the late nineteenth-century Peru. Analyzing this character implies to tackle the complex and at times contradictory risks that Peruvian intellectuals —in this case, a woman— took towards modernity in said period, and the resistance imposed by conservative groups on these literary avant-gardes. Using her novels and newspaper articles, we addressed the intellectual career of Clorinda Matto in the 1880s and 1890s, considering her proposals for the modernization of public life. In particular, her approaches to female education, which earned her the clerical and conservative opposition that ended up motivating her participation, from the press, in political life, and finally, her exile.